2010
DOI: 10.1371/journal.pone.0012694
|View full text |Cite
|
Sign up to set email alerts
|

Increase on the Initial Soluble Heme Levels in Acidic Conditions Is an Important Mechanism for Spontaneous Heme Crystallization In Vitro

Abstract: BackgroundHemozoin (Hz) is a heme crystal that represents a vital pathway for heme disposal in several blood-feeding organisms. Recent evidence demonstrated that β-hematin (βH) (the synthetic counterpart of Hz) formation occurs under physiological conditions near synthetic or biological hydrophilic-hydrophobic interfaces. This seems to require a heme dimer acting as a precursor of Hz crystals that would be formed spontaneously in the absence of the competing water molecules bound to the heme iron. Here, we aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…The differences in morphology between dioleoyl-PC and dipalmitoyl-PC vesicles were probably due to their different physical properties, in particular the different states – fluid or gel – caused by the differences in T m values. Moreover, since the hydrophobic interactions between their inducers and heme have been proposed as an important force in the creation of a precursor heme dimer [38], [45], [54], [55], it was interesting to explore the correlation between the physical properties of phospholipids and their ability to induce BH. Our results demonstrated that phospholipids could induce BH formation only in the fluid phase, and could not do so in the gel phase.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in morphology between dioleoyl-PC and dipalmitoyl-PC vesicles were probably due to their different physical properties, in particular the different states – fluid or gel – caused by the differences in T m values. Moreover, since the hydrophobic interactions between their inducers and heme have been proposed as an important force in the creation of a precursor heme dimer [38], [45], [54], [55], it was interesting to explore the correlation between the physical properties of phospholipids and their ability to induce BH. Our results demonstrated that phospholipids could induce BH formation only in the fluid phase, and could not do so in the gel phase.…”
Section: Discussionmentioning
confidence: 99%
“…The highest absorbance of such solutions, in the Soret band near 400 nm, is below 0.1. Hence, spectroscopic determination of concentrations below this limit is prone to high error [25]. …”
Section: Methodsmentioning
confidence: 99%
“…The energy barrier to crystal nucleus formation is known to depend on surface tension (Myerson, 1993), so the authors proposed that alcohols also play a role in reducing the energy barrier to crystallisation in this way. A recent study on -haematin formation in aqueous DMSO and solutions of several polyethylene glycols (PEGs) has provided direct support for the solubilisation hypothesis (Stiebler et al, 2010b). In this investigation it was demonstrated spectrophotometrically that Fe(III)PPIX solubility at pH 4.8 in 0.5 M acetate buffer increases linearly with increasing DMSO concentration and that the yield of -haematin is directly proportional to the solubility of Fe(III)PPIX in this medium.…”
Section: -Haematin Formation In Homogeneous Solvent Systemsmentioning
confidence: 61%